Juridical background and consequensces of partisan leadership recognition - Gailius, Bernardas (Genocidas ir rezistencija, 2006)
The Seimas of the Republic of Lithuania has repeatedly stipulated in its laws that the Lithuanian partisan leadership was the legitimate government of the occupied state. Although the recognition of the authority of the partisan leadership is of great significance for many legal issues related to that period, there is neither case law supplementing the legal provisions nor doctrinal interpretation of those provisions. Apparently, the most important reason for this is that the assertion that the partisan leadership was "the only legitimate authority on the territory of occupied Lithuania" is rejected in advance as declarative and unfounded. It is therefore worth considering as to whether and why such an assertion is meaningful, as well as the consequences of stipulating it in law. Partisans were a force which, broadly speaking, enjoyed a mandate from the people and, based on that mandate, as well as international and national law, defended the state against aggression by force of arms, and were therefore an organisation of the kind that is commonly referred to as an army. Moreover, this organisation had a mandate to act on behalf of the people and the state, which meant that the Lithuanian population had to obey it.
Keywords: partisans; law; partisans leaders; international law